1999
DOI: 10.1007/s002449900442
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mercury and Other Trace Metals in the Cockle Cerastoderma glaucum from the Mediterranean Lagoon Etang de Thau

Abstract: The concentrations of Ag, Cd, Co, Cr, Cu, Ni, Pb, Zn, Mn, and Fe in the soft tissue of the cockle Cerastoderma glaucum from six sites along the Mediterranean Lagoon Etang de Thau were determined by AAS; Hg was determined by the cold-vapor technique. Significant spatial variations in metal concentrations within the lagoon were recorded. Elevated levels of tissue Pb, Cr, and Hg in the Etang des Eaux Blanches, an area adjacent to the harbor and highly industrialized region, are likely of anthropogenic origin. Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…However there are no studies about the cockle C. glaucum. This species was validated in previous studies as a biomonitor organism showing correlation between site contamination and metal accumulation (Szefer and Szefer 1985;Szefer and Wolowicz 1993;Arjonilla et al 1994;Szefer et al 1999;Machreki-Ajmi and Hamza-Chaffai 2006). Moreover, C. glaucum lives in the superficial sediment, and together with R. decussatus could provide a couple of bivalves for pollution biomonitoring along Tunisian coasts.…”
Section: Introductionmentioning
confidence: 91%
“…However there are no studies about the cockle C. glaucum. This species was validated in previous studies as a biomonitor organism showing correlation between site contamination and metal accumulation (Szefer and Szefer 1985;Szefer and Wolowicz 1993;Arjonilla et al 1994;Szefer et al 1999;Machreki-Ajmi and Hamza-Chaffai 2006). Moreover, C. glaucum lives in the superficial sediment, and together with R. decussatus could provide a couple of bivalves for pollution biomonitoring along Tunisian coasts.…”
Section: Introductionmentioning
confidence: 91%
“…Metal bioaccumulation in soft tissues of cockles (SZEFER et al, 1999), mussels (LABONNE, BEN OTHMAN, and LUCK, 2001), and oysters (AMIARD et al, 2007) from the Thau Lagoon has also been documented. Nevertheless, metal concentrations in shellfish monitored by the French National Observation Network (RNO, IFREMER) have never exceeded the maximum allowed concentrations for consumption as determined by EU regulations.…”
Section: Introductionmentioning
confidence: 92%
“…In other bivalves, Patel and Anthony [74] reported that the highest Cd concentration was found in the gills of Anadara granosa. Szefer et al [75] found that the gills of cockle Cerastoderma glaucum contained highest concentrations of Co and Ni than other organs. The high bioconcentration factor in a metal free medium in mussel gills indicated that the gills were the sites of dominance for Pb and Zn assimilation in M. edulis [76].…”
Section: Fig 1 -High Bioaccumulation Ability Of Mya Arenaria For Butmentioning
confidence: 99%